Theoretical Aspects of Creating the Business Models for Supply Chain Process of Industrial Enterprises - Osipov, Victor A.; Astakhova, Ekaterina Vi. (International Journal of Supply Chain Management, 2018)
Abstract- Creating the business models for supply chain process is the subject of modern scientific research in the field of strategic planning and management of the enterprise. Some theoretical and practical aspects have not yet received a comprehensive scientific substantiation. General problem of enterprise management is traditionally analyzed in the researches, and business modeling is not fully investigated. The current state of the economy and peculiarities of its development, as well as the transformational nature of the Russian economy, show that the most important theoretical and practical aspects, which require scientific attention and development, analysis and systematization, are the theoretical provisions of business modeling concept for supply chain process; clarification of the term "business model" for supply chain process of an industrial enterprise; definition of the main elements and substantiation of the technology of business model formation; systematization and generalization of modern methods of strategic analysis; formation of an integrated system for assessment the effectiveness of the enterprise’s business model for supply chain process. The issues of strategic development of the enterprise always arouse a great interest among researchers. Today, a significant number of business models have been created for the development of enterprises of various industry structures. The purpose of the article is to systematize the information about the creation of business models for supply chain process of industrial enterprises, to consider the features of the models use at the present stage. Scientific and theoretical basis of the research was the methods of analysis and synthesis, scientific abstraction, the use of quantitative and qualitative assessment methods, with the help of which the categories of the concept business model for the supply chain process were defined. Endogenous and exogenous factors, influencing the functioning of enterprises’ business models were identified. The article deals with the conceptual issues of the business model for the supply chain process formation, in particular, the essence and peculiarities of modern business models, as well as management approaches to the processes of development of enterprise’s business model for supply chain process.   Keywords: business model, strategic development, industrial enterprise, supply chain process, creation.